Wear-resistant high-toughness concrete material suitable for fabricated pavement slab and preparation method of wear-resistant high-toughness concrete material
By using limestone, burning clay and regenerative microfimpen in the concrete materials of prefabricated palettes, combined with LC3 cement and carbon dioxide carbonization technology, the problem of cracking in traditional concrete road panels during hanging and transportation has improved the resistance of the material Gratitude and durability, while reducing carbon emissions and production costs.
Patent Information
- Application Number
- CN202411306603.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-28
AI Technical Summary
Traditional prefabricated concrete pavement panels are prone to cracks during lifting and transportation, affecting durability. At the same time, the use of quartz sand leads to high costs, large carbon emissions, and poor wear resistance.
By incorporating lime stones and burning clay to reduce the amount of cement and reduce carbon emissions; add regenerative microfream to the LC3 cement as aggregate, and use carbon dioxide carbonization to form aggregate to improve the toughness and compressive strength of the material.
It significantly improves the toughness, compressive strength and durability of concrete, reducing carbon emissions and production costs, and improving the wear resistance of materials.
Smart Images

Figure BDA0005049403280000091 
Figure BDA0005049403280000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete material preparation, and in particular relates to a wear-resistant and high-toughness concrete material suitable for assembled road panels and a preparation method thereof. Background Art
[0002] At present, the mileage of highways that need maintenance accounts for more than 99% of the total mileage of highways. Traditional maintenance methods are noisy and dusty, which disturbs people, so fast and green maintenance is needed. Prefabricated concrete road panels are prefabricated in factories and installed on site, which is one of the ways to achieve fast and green maintenance. Prefabricated concrete road panels need to be hoisted and transported. Ordinary concrete has a large weight and is prone to cracks during hoisting and transportation, affecting the durability of concrete. Therefore, in order to improve the durability of concrete, fine aggregates, quartz sand, and a large amount of cement are usually added, which will lead to poor wear resistance of concrete, large cement consumption, high carbon emissions, and the use of quartz sand, which is costly.
[0003] Therefore, there is an urgent need for a wear-resistant and high-toughness concrete material suitable for assembled road panels and a preparation method thereof to solve the above technical problems. Summary of the invention
[0004] The purpose of the embodiment of the present invention is to provide a wear-resistant and high-toughness concrete material suitable for assembled road panels and a preparation method thereof, which reduces the amount of cement and reduces carbon emissions by adding limestone and calcined clay; recycled micropowder is added to LC3 cement, and the particles formed by carbonization are used as aggregate for preparation. The obtained material has the advantages of good toughness, high compressive strength and durability, low carbon emissions, etc., thereby solving at least one technical problem involved in the background technology.
[0005] In order to solve the above-mentioned technical problems, the present invention is achieved as follows:
[0006] The embodiment of the present invention provides a wear-resistant and high-toughness concrete material suitable for assembled road panels, which includes, by weight, 200-300 parts of calcined clay, 100-200 parts of limestone, 220-350 parts of cement clinker, 100-300 parts of recycled micropowder, 5-15 parts of fiber, 150-250 parts of water, 5-15 parts of polyacrylamide, and 5-15 parts of CaO.
[0007] Optionally, the cement is PO42.5R ordinary Portland cement with a cement density of 340 g / cm 3 .
[0008] Optionally, the calcined clay includes Al2O3, SiO2, and Fe2O3 accounting for more than 96% of the mass of the calcined clay.
[0009] Optionally, the density of the limestone is 2930 kg / m 3 , loss on ignition 43.50%, moisture content 0.2%.
[0010] Optionally, the fiber is PVA fiber with a diameter of 3-12 mm.
[0011] Optionally, the concentration of the polyacrylamide is 0.2×10 –7 -1.0×10 -7 mol / L.
[0012] The present invention also provides a method for preparing the wear-resistant and high-toughness concrete material suitable for assembled road panels, comprising the following steps:
[0013] Step 1: providing, by weight, 200-300 parts of calcined clay, 100-200 parts of limestone, 220-350 parts of cement clinker, 100-300 parts of recycled micropowder, 5-15 parts of fiber, 150-250 parts of water, 5-15 parts of polyacrylamide, and 5-15 parts of CaO;
[0014] Step 2, putting the regenerated micro powder into water, dissolving polyacrylamide in 100 ml of distilled water at a temperature of 80° C., to prepare an organic substrate;
[0015] Step 3, then dissolve 5-15 parts of CaO in 100 ml of 80°C distilled water for digestion to form a Ca(OH)2 slurry;
[0016] Step 4: Blow a mixed gas of CO2 and N2 into the Ca(OH)2 slurry at a flow rate of 1-5 l / min, and control the reaction by the pH value of the culture medium at 80°C. When the pH value reaches 7, stop the reaction, induce the formation of aragonite, and agglomerate the carbonized products of the regenerated micropowder to form aggregate;
[0017] Step 5, putting calcined clay, limestone and cement clinker into a mixer and stirring for a certain time, then adding water and continuing to stir for a certain time;
[0018] Step 6: Add aggregate and fiber into a mixer and stir for a certain period of time to obtain concrete slurry, which is then poured into a mold;
[0019] Step seven, leaving the mold at room temperature for a certain period of time, after the slurry is formed, demolding to obtain a test block, placing the test block in a standard curing box for curing, and obtaining a wear-resistant and high-toughness concrete material suitable for assembled road panels.
[0020] Optionally, in step four, the CO2 concentration is 10%-30%, and the N2 concentration is.
[0021] Optionally, in step 5, cement clinker is put into a mixer and stirred for 2 minutes, and water is added and stirring is continued for 2 minutes.
[0022] Optionally, in step six, the aggregate and fiber are added to the mixer and stirred for 10 minutes.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The limestone calcined clay cement (LC3) is mainly used. Compared with ordinary cement, by adding limestone and calcined clay to the original Portland cement system to replace the traditional Portland cement clinker, it can significantly reduce the carbon dioxide emissions and energy consumption in the traditional cement production process;
[0025] (2) Compared with traditional high-toughness concrete materials, quartz sand is generally used as fine aggregate, but the production cost is relatively high due to the cost and scarcity of quartz sand resources; the present invention uses recycled micropowder as fine aggregate, which not only solves the cost problem, but also makes the aragonite formed after carbonization agglomerate around the recycled micropowder, which has clear edges and corners compared to quartz sand, and is more conducive to improving the wear resistance of the material; at the same time, carbon dioxide needs to be used in the preparation process, which can further reduce carbon emissions. Therefore, the fine aggregate used in the present invention is of great significance to protecting the environment and reducing resource waste. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The embodiment of the present invention provides a wear-resistant and high-toughness concrete material suitable for assembled road panels, which includes, by weight, 200-300 parts of calcined clay, 100-200 parts of limestone, 220-350 parts of cement clinker, 100-300 parts of recycled micropowder, 5-15 parts of fiber, 150-250 parts of water, 5-15 parts of polyacrylamide, and 5-15 parts of CaO.
[0028] The cement is PO42.5R ordinary Portland cement, with a cement density of 340g / cm 3 .
[0029] The calcined clay comprises Al2O3, SiO2, and Fe2O3 accounting for more than 96% of the mass of the calcined clay. Specifically, Al2O3, SiO2, and Fe2O3 account for 96.18% of the mass of the calcined clay, and other chemical components only account for 3.82%.
[0030] The density of the limestone is 2930 kg / m 3, loss on ignition 43.50%, moisture content 0.2%.
[0031] The fiber is PVA fiber with a diameter of 3-12 mm.
[0032] The concentration of the polyacrylamide is 0.2×10 –7 -1.0×10 -7 mol / L.
[0033] The water is high-purity distilled water.
[0034] The present invention also provides a method for preparing the wear-resistant and high-toughness concrete material suitable for assembled road panels, comprising the following steps:
[0035] Step 1: providing, by weight, 200-300 parts of calcined clay, 100-200 parts of limestone, 220-350 parts of cement clinker, 100-300 parts of recycled micropowder, 5-15 parts of fiber, 150-250 parts of water, 5-15 parts of polyacrylamide, and 5-15 parts of CaO;
[0036] Step 2, putting the regenerated micro powder into water, dissolving polyacrylamide in 100 ml of distilled water at a temperature of 80° C., to prepare an organic substrate;
[0037] Step 3, then dissolve 5-15 parts of CaO in 100 ml of 80°C distilled water for digestion to form a Ca(OH)2 slurry;
[0038] Step 4: Blow a mixed gas of CO2 and N2 into the Ca(OH)2 slurry at a flow rate of 1-5 L / min, and control the carbonization reaction by the pH value of the culture medium at 80°C. When the pH value reaches 7, stop the reaction, induce the formation of aragonite, and agglomerate the carbonized products of the regenerated micropowder to form aggregate;
[0039] Step 5: put the calcined clay, limestone and cement clinker into a mixer and stir for 2 minutes, then add water and continue stirring for 2 minutes;
[0040] Step 6: Add aggregate and fiber into a mixer and stir for 10 minutes to obtain concrete slurry, which is then poured into a mold;
[0041] Step seven, leaving the mold at room temperature for 24 hours, after the slurry is formed, demolding to obtain a test block, placing the test block in a standard curing box for curing, and obtaining a wear-resistant and high-toughness concrete material suitable for assembled road panels.
[0042] In step 4, the CO2 concentration is 10%-30%, and N2 is pure nitrogen. In addition, in this step, the principle of the carbonization reaction is:
[0043] CO2 and Ca(OH)2 will generate calcium carbonate, which has three crystal forms, namely square calcite, spherical vaterite and fibrous aragonite. Generally, CO2 and Ca(OH)2 react to generate square calcite. Then, since polyacrylamide is added in advance in the present invention and the reaction is carried out at a high temperature of 80 degrees, the carbonization reaction will be affected, and the calcium carbonate formed is fibrous aragonite, thereby improving the wear resistance.
[0044] In step 5, cement clinker is put into a mixer and stirred for 2 minutes, and water is added and stirring is continued for 2 minutes.
[0045] In step six, aggregate and fiber are added into the mixer and mixed for 10 minutes.
[0046] The preparation method of the wear-resistant and high-toughness concrete material suitable for assembled road panels provided by the present invention is described in detail below with reference to specific examples 1-7 and comparative example 1.
[0047] Example 1
[0048] Embodiment 1 provides a method for preparing a wear-resistant and high-toughness concrete material suitable for assembled road panels, comprising the following steps:
[0049] (1) 200 parts of regenerated micropowder are put into water, and 10 parts of polyacrylamide are dissolved in 100 ml of distilled water at a temperature of 80°C to prepare an organic substrate, wherein the concentration of polyacrylamide is 0.25×10-7 mol / L;
[0050] (2) 10 parts of CaO were dissolved in 100 ml of 80° C. distilled water for digestion to form a Ca(OH)2 slurry, and a mixed gas of CO2 and N2 was blown into the Ca(OH)2 slurry at a flow rate of 1 L / min, with a CO2 concentration of 20%; at 80° C., the reaction was controlled by the pH value of the culture medium, and when the pH value reached about 7, the reaction was stopped to induce the formation of aragonite, and the carbonized products of the micropowders were agglomerated to form aggregates;
[0051] (3) 260 parts of calcined clay, 195 parts of limestone, and 300 parts of cement clinker were placed in a mixer and stirred for 2 minutes, and 190 parts of water were added and stirred for another 2 minutes;
[0052] (4) 180 parts of aggregate and 10 parts of fiber were added to a mixer and stirred for 10 minutes to obtain a concrete slurry, which was poured into a mold;
[0053] (5) The mold is left to stand at room temperature for 24 hours to wait for the slurry to form. After 24 hours, the formed test block is demolded and then placed in a standard curing box for curing to obtain a wear-resistant and high-toughness concrete material suitable for prefabricated road panels.
[0054] Example 2
[0055] Embodiment 2 provides a method for preparing a wear-resistant and high-toughness concrete material suitable for assembled road panels, comprising the following steps:
[0056] (1) 200 parts of regenerated micropowder are put into water, and 10 parts of polyacrylamide are dissolved in 100 ml of distilled water at a temperature of 80°C to prepare an organic substrate, wherein the concentration of polyacrylamide is 0.25×10-7 mol / L;
[0057] (2) 10 parts of CaO are dissolved in 100 ml of 80° C. distilled water for digestion to form a Ca(OH)2 slurry, and a mixed gas of CO2 and N2 is blown into the Ca(OH)2 slurry at a flow rate of 2 L / min, with a CO2 concentration of 20%; at 80° C., the reaction is controlled by the pH value of the culture medium, and the reaction is stopped when the pH value reaches about 7, which can induce the formation of aragonite, and the carbonized products of the micropowders are agglomerated to form aggregates;
[0058] (3) 260 parts of calcined clay, 195 parts of limestone, and 300 parts of cement clinker were placed in a mixer and stirred for 2 minutes, and 190 parts of water were added and stirred for another 2 minutes;
[0059] (4) 180 parts of aggregate and 10 parts of fiber were added to a mixer and stirred for 10 minutes to obtain a concrete slurry, which was poured into a mold;
[0060] (5) The mold is left to stand at room temperature for 24 hours to wait for the slurry to form. After 24 hours, the formed test block is demolded and then placed in a standard curing box for curing to obtain a wear-resistant and high-toughness concrete material suitable for prefabricated road panels.
[0061] Example 3
[0062] Embodiment 3 provides a method for preparing a wear-resistant and high-toughness concrete material suitable for assembled road panels, comprising the following steps:
[0063] (1) 200 parts of regenerated micropowder are put into water, and 10 parts of polyacrylamide are dissolved in 100 ml of distilled water at a temperature of 80°C to prepare an organic substrate, wherein the concentration of polyacrylamide is 0.25×10-7 mol / L;
[0064] (2) 10 parts of CaO are dissolved in 100 ml of 80° C. distilled water for digestion to form a Ca(OH)2 slurry, and a mixed gas of CO2 and N2 is blown into the Ca(OH)2 slurry at a flow rate of 3 L / min, with a CO2 concentration of 20%; at 80° C., the reaction is controlled by the pH value of the culture medium, and the reaction is stopped when the pH value reaches about 7, which can induce the formation of aragonite, and the carbonized products of the micropowders are agglomerated to form aggregates;
[0065] (3) 260 parts of calcined clay, 195 parts of limestone, and 300 parts of cement clinker were placed in a mixer and stirred for 2 minutes, and 190 parts of water were added and stirred for another 2 minutes;
[0066] (4) 180 parts of aggregate and 10 parts of fiber were added to a mixer and stirred for 10 minutes to obtain a concrete slurry, which was poured into a mold;
[0067] (5) The mold is left to stand at room temperature for 24 hours to wait for the slurry to form. After 24 hours, the formed test block is demolded and then placed in a standard curing box for curing to obtain a wear-resistant and high-toughness concrete material suitable for prefabricated road panels.
[0068] Example 4
[0069] Embodiment 4 provides a method for preparing a wear-resistant and high-toughness concrete material suitable for assembled road panels, comprising the following steps:
[0070] (1) 200 parts of regenerated micropowder are put into water, and 10 parts of polyacrylamide are dissolved in 100 ml of distilled water at a temperature of 80°C to prepare an organic substrate, wherein the concentration of polyacrylamide is 0.25×10-7 mol / L;
[0071] (2) 10 parts of CaO are dissolved in 100 ml of 80° C. distilled water for digestion to form a Ca(OH)2 slurry, and a mixed gas of CO2 and N2 is blown into the Ca(OH)2 slurry at a flow rate of 2 L / min, with a CO2 concentration of 10%; at 80° C., the reaction is controlled by the pH value of the culture medium, and the reaction is stopped when the pH value reaches about 7, which can induce the formation of aragonite, and the carbonized products of the micropowders are agglomerated to form aggregates;
[0072] (3) 260 parts of calcined clay, 195 parts of limestone, and 300 parts of cement clinker were placed in a mixer and stirred for 2 minutes, and 190 parts of water were added and stirred for another 2 minutes;
[0073] (4) 180 parts of aggregate and 10 parts of fiber were added to a mixer and stirred for 10 minutes to obtain a concrete slurry, which was poured into a mold;
[0074] (5) The mold is left to stand at room temperature for 24 hours to wait for the slurry to form. After 24 hours, the formed test block is demolded and then placed in a standard curing box for curing to obtain a wear-resistant and high-toughness concrete material suitable for prefabricated road panels.
[0075] Example 5
[0076] Example 5 provides a method for preparing a wear-resistant and high-toughness concrete material suitable for assembled road panels, comprising the following steps:
[0077] (1) 200 parts of regenerated micropowder are put into water, and 10 parts of polyacrylamide are dissolved in 100 ml of distilled water at a temperature of 80°C to prepare an organic substrate, wherein the concentration of polyacrylamide is 0.25×10-7 mol / L;
[0078] (2) 10 parts of CaO are dissolved in 100 ml of 80° C. distilled water for digestion to form a Ca(OH)2 slurry, and a mixed gas of CO2 and N2 is blown into the Ca(OH)2 slurry at a flow rate of 2 L / min, with a CO2 concentration of 30%; at 80° C., the reaction is controlled by the pH value of the culture medium, and the reaction is stopped when the pH value reaches about 7, which can induce the formation of aragonite, and the carbonized products of the micropowders are agglomerated to form aggregates;
[0079] (3) 260 parts of calcined clay, 195 parts of limestone, and 300 parts of cement clinker were placed in a mixer and stirred for 2 minutes, and 190 parts of water were added and stirred for another 2 minutes;
[0080] (4) 180 parts of aggregate and 10 parts of fiber were added to a mixer and stirred for 10 minutes to obtain a concrete slurry, which was poured into a mold;
[0081] (5) The mold is left to stand at room temperature for 24 hours to wait for the slurry to form. After 24 hours, the formed test block is demolded and then placed in a standard curing box for curing to obtain a wear-resistant and high-toughness concrete material suitable for prefabricated road panels.
[0082] Example 6
[0083] Example 6 provides a method for preparing a wear-resistant and high-toughness concrete material suitable for assembled road panels, comprising the following steps:
[0084] (1) 200 parts of regenerated micropowder are put into water, and 10 parts of polyacrylamide are dissolved in 100 ml of distilled water at a temperature of 80°C to prepare an organic substrate, wherein the concentration of polyacrylamide is 0.5×10-7 mol / L;
[0085] (2) 10 parts of CaO are dissolved in 100 ml of 80° C. distilled water for digestion to form a Ca(OH)2 slurry, and a mixed gas of CO2 and N2 is blown into the Ca(OH)2 slurry at a flow rate of 2 L / min, with a CO2 concentration of 30%; at 80° C., the reaction is controlled by the pH value of the culture medium, and the reaction is stopped when the pH value reaches about 7, which can induce the formation of aragonite, and the carbonized products of the micropowders are agglomerated to form aggregates;
[0086] (3) 260 parts of calcined clay, 195 parts of limestone, and 300 parts of cement clinker were placed in a mixer and stirred for 2 minutes, and 190 parts of water were added and stirred for another 2 minutes;
[0087] (4) 180 parts of aggregate and 10 parts of fiber were added to a mixer and stirred for 10 minutes to obtain a concrete slurry, which was poured into a mold;
[0088] (5) The mold is left to stand at room temperature for 24 hours to wait for the slurry to form. After 24 hours, the formed test block is demolded and then placed in a standard curing box for curing to obtain a wear-resistant and high-toughness concrete material suitable for prefabricated road panels.
[0089] Example 7
[0090] Example 7 provides a method for preparing a wear-resistant and high-toughness concrete material suitable for assembled road panels, comprising the following steps:
[0091] (1) 200 parts of regenerated micropowder are put into water, and 10 parts of polyacrylamide are dissolved in 100 ml of distilled water at a temperature of 80° C. to prepare an organic substrate, wherein the concentration of polyacrylamide is 0.75×10-7 mol / L;
[0092] (2) 10 parts of CaO are dissolved in 100 ml of 80° C. distilled water for digestion to form a Ca(OH)2 slurry, and a mixed gas of CO2 and N2 is blown into the Ca(OH)2 slurry at a flow rate of 2 L / min, with a CO2 concentration of 30%; at 80° C., the reaction is controlled by the pH value of the culture medium, and the reaction is stopped when the pH value reaches about 7, which can induce the formation of aragonite, and the carbonized products of the micropowders are agglomerated to form aggregates;
[0093] (3) 260 parts of calcined clay, 195 parts of limestone, and 300 parts of cement clinker were placed in a mixer and stirred for 2 minutes, and 190 parts of water were added and stirred for another 2 minutes;
[0094] (4) 180 parts of aggregate and 10 parts of fiber were added to a mixer and stirred for 10 minutes to obtain a concrete slurry, which was poured into a mold;
[0095] (5) The mold is left to stand at room temperature for 24 hours to wait for the slurry to form. After 24 hours, the formed test block is demolded and then placed in a standard curing box for curing to obtain a wear-resistant and high-toughness concrete material suitable for prefabricated road panels.
[0096] Comparative Example 1
[0097] Comparative Example 1 provides a method for preparing a concrete material, comprising the following steps:
[0098] (1) 260 parts of calcined clay, 195 parts of limestone, and 300 parts of cement clinker were placed in a mixer and stirred for 2 minutes, and 190 parts of water were added and stirred for another 2 minutes;
[0099] (2) 180 parts of quartz sand and 10 parts of fiber were added to a mixer and stirred for 10 minutes to obtain a concrete slurry, which was poured into a mold;
[0100] (3) The mold is left to stand at room temperature for 24 hours to wait for the slurry to form. After 24 hours, the formed test block is demolded and then placed in a standard curing box for curing to obtain a concrete material.
[0101] The average particle size of the aggregate prepared in Examples 1 to 7 was tested. The obtained wear-resistant and high-toughness concrete material suitable for assembled road panels was poured into a mold, demolded after curing at room temperature for 1 day, and placed in a high-humidity and normal-temperature environment for 27 days of curing, and then tested for compressive strength and wear resistance. The wear resistance was characterized by the wear loss per unit area. The test results are shown in Table 1.
[0102] Table 1 Compressive strength and wear resistance test results
[0103]
[0104]
[0105] As shown in Table 1, the aggregate particle size in Comparative Example 1 is small and the wear resistance is low. The artificial aggregate prepared by carbonized recycled micropowder has significantly improved the wear resistance of concrete. With the increase of gas flow rate, carbon dioxide concentration and polyacrylamide concentration, the particle size of artificial aggregate gradually increases and the wear resistance of concrete gradually improves. As described above, the preparation of wear-resistant and high-toughness concrete material suitable for assembled road panels is completed, which can be widely used in highway engineering construction.
[0106] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0107] In addition, it should be noted that the scope of the methods and systems in the embodiments of the present invention is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved. For example, the described methods may be performed in an order different from that described, and various steps may be added, omitted, or combined. In addition, features described with reference to certain examples may be combined in other examples.
[0108] The embodiments of the present invention are described above, but the present invention is not limited to the above-mentioned specific implementation modes. The above-mentioned specific implementation modes are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the purpose of the present invention and the claims, all of which are protected by the present invention.
Claims
1. A wear-resistant and high-toughness concrete material suitable for assembled road panels, characterized in that: Calculated by weight, it includes 200-300 parts of calcined clay, 100-200 parts of limestone, 220-350 parts of cement clinker, 100-300 parts of recycled micro powder, 5-15 parts of fiber, 150-250 parts of water, 5-15 parts of polyacrylamide, and 5-15 parts of CaO.
2. The wear-resistant and high-toughness concrete material suitable for assembled road panels according to claim 1 is characterized in that: The cement is PO42.5R ordinary Portland cement, with a cement density of 340g / cm 3 .
3. The wear-resistant and high-toughness concrete material suitable for assembled road panels according to claim 1, characterized in that: The calcined clay comprises Al2O3, SiO2 and Fe2O3 accounting for more than 96% of the mass of the calcined clay.
4. The wear-resistant and high-toughness concrete material suitable for assembled road panels according to claim 1, characterized in that: The density of the limestone is 2930 kg / m 3 , loss on ignition 43.50%, moisture content 0.2%.
5. The wear-resistant and high-toughness concrete material suitable for assembled road panels according to claim 1, characterized in that: The fiber is PVA fiber with a diameter of 3-12 mm.
6. The wear-resistant and high-toughness concrete material suitable for assembled road panels according to claim 1, characterized in that: The concentration of the polyacrylamide is 0.2×10 –7 -1.0×10 -7 mol / L.
7. A method for preparing the wear-resistant and high-toughness concrete material suitable for assembled road panels according to any one of claims 1 to 6, characterized in that: The steps include: Step 1: providing, by weight, 200-300 parts of calcined clay, 100-200 parts of limestone, 220-350 parts of cement clinker, 100-300 parts of recycled micropowder, 5-15 parts of fiber, 150-250 parts of water, 5-15 parts of polyacrylamide, and 5-15 parts of CaO; Step 2, putting the regenerated micro powder into water, dissolving polyacrylamide in 100 ml of distilled water at a temperature of 80° C., to prepare an organic substrate; Step 3, then dissolve 5-15 parts of CaO in 100 ml of 80°C distilled water for digestion to form a Ca(OH)2 slurry; Step 4: Blow a mixed gas of CO2 and N2 into the Ca(OH)2 slurry at a flow rate of 1-5 L / min, and control the carbonization reaction by the pH value of the culture medium at 80°C. When the pH value reaches 7, stop the reaction, induce the formation of aragonite, and agglomerate the carbonized products of the regenerated micropowder to form aggregate; Step 5, putting calcined clay, limestone and cement clinker into a mixer and stirring for a certain time, then adding water and continuing to stir for a certain time; Step 6: Add aggregate and fiber into a mixer and stir for a certain period of time to obtain concrete slurry, which is then poured into a mold; Step seven, leaving the mold at room temperature for a certain period of time, after the slurry is formed, demolding to obtain a test block, placing the test block in a standard curing box for curing, and obtaining a wear-resistant and high-toughness concrete material suitable for assembled road panels.
8. The preparation method according to claim 7, characterized in that: In step 4, the CO2 concentration is 10%-30%, and the N2 concentration is.
9. The preparation method according to claim 7, characterized in that: In step 5, cement clinker is put into a mixer and stirred for 2 minutes, and water is added and stirring is continued for 2 minutes.
10. The preparation method according to claim 7, characterized in that: In step six, aggregate and fiber are added to the mixer and mixed for 10 minutes.